Investigation of the Efficacy of Adjunctive Therapy with Bioavailability‐Boosted Curcuminoids in Major Depressive Disorder - Panahi, Yunes; Badeli, Roghayeh; Karami, Gholam‐Reza; Sahebkar, Amirhossein (Phytotherapy research, 2015)
Current medications have limited efficacy in controlling the symptoms of major depressive disorder (MDD), and are associated with several adverse events on long‐term use. Curcuminoids are extremely safe and multifunctional phytopharmaceuticals that have been shown to alleviate depressive symptoms in a variety of experimental models. The present study aimed to investigate the efficacy of curcuminoids as an add‐on to standard antidepressants in patients with MDD. One hundred and eleven subjects were assigned to standard antidepressive therapy plus curcuminoids–piperine combination (1000–10 mg/day; n = 61) or standard antidepressive therapy alone (n = 50) for a period of 6 weeks. Efficacy measures were changes in the psychological status on the basis of the Hospital Anxiety and Depression Scale (HADS) and Beck Depression Inventory II (BDI‐II). The BDI‐II and HADS total and subscale scores were reduced by the end of trial in both study groups. There were significantly greater reductions in total HADS score and subscales of anxiety and depression in the curcuminoids versus control group (p < 0.001). Likewise, reductions in BDI‐II total score and scores of somatic and cognitive subscales were found to be greater in the curcuminoids compared with control group (p < 0.001). Co‐administration of curcuminoids with piperine may be used as a safe and effective add‐on to standard antidepressants in patients with MDD. Copyright © 2014 John Wiley & Sons, Ltd.